Vascular Remodeling, Oxidative Stress, and Disrupted PPARγ Expression in Rats of Long-Term Hyperhomocysteinemia with Metabolic Disturbance. (15th January 2018) - Huo, Yajing; Wu, Xuqing; Ding, Jing; Geng, Yang; Qiao, Weiwei; Ge, Anyan; Guo, Cen; Lv, Jianing; Bao, Haifeng; Fan, Wei
Abstract : Hyperhomocysteinemia, a risk factor for vascular disease, is associated with metabolic syndrome. Our study was aimed at exploring the effect of long-term hyperhomocysteinemia with metabolic disturbances on vascular remodeling. We also studied oxidative stress and expression of PPAR γ in the coronary arteriole as a possible mechanism underlying vascular remodeling. Rats were treated with standard rodent chow (Control) or diet enriched in methionine (Met) for 48 weeks. Plasma homocysteine, blood glucose, serum lipids, malondialdehyde (MDA), superoxide dismutase (SOD), and nitric oxide (NO) levels were measured. Coronary arteriolar and carotid arterial remodeling was assessed by histomorphometric techniques and the expression of PPAR γ in vessel wall was investigated. In Met group, an increase in the level of fasting blood glucose, serum triglyceride, total cholesterol, MDA, and NO, a decline in the serum SOD level, and increased collagen deposition in coronary and carotid arteries were found. Moreover, we detected decreased expression of PPAR γ in the coronary arterioles in Met group. In summary, our study revealed metabolic disturbances in this model of long-term hyperhomocysteinemia together with vascular remodeling and suggested that impaired oxidative stress, endothelium dysfunction, and decreased PPAR γ expression in the vessel wall could be underlying mechanisms.